Development of a Novel T-tube Frontal Sinus Irrigation Catheter. Issue 5 (September 2016) - Rotenberg, Brian W.; Ioanidis, Khrystyna E.; Sowerby, Leigh J.
Background: The problem of postoperative management after frontal sinus surgery remains a challenge. The bilateral opening created in the Draf III procedure does not fit any currently available stent, and patients find rinsing the frontal sinus difficult, which thus decreases compliance. The objective of this study was to demonstrate the successful use of a novel frontal sinus catheter fashioned from a biliary T tube by addressing these issues in patients with complicated sinus disease. Methods: This was a review of 30 patients who underwent a Draf III procedure between January and October 2014, and who had a T-tube stent inserted at the end of the procedure. Patient charts were analyzed for complications such as bleeding, infection, and restenosis as well as indications of ease of rinsing ability after surgery. Results: From the chart data, there was only one intraoperative bleed and only one postoperative bleed that required packing. Four patients had infections that required antibiotics after surgery. At the time of data collection, only one patient had signs of restenosis as judged by the operating surgeon. Patients reported an ease of rinsing ability with the T-tube stent. Conclusions: The novel biliary T-tube stent use presented in this article is a promising future direction for postoperative care after extended frontal sinus surgery.